To a Question about the Criteria and Parameters of the Effectiveness of the Government in Democratic Countries - ABRAMOV, Ruslan A.; MUKHAEV, Rashid T.; SOKOLOV, Maxim S. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Effective public management activities are an important factor in the development of the modern state, the key to social progress. Management as a scientific organization activity is an essential element in the efficient and effective functioning of government. Estimation of efficiency of public administration is needed for both public authorities and society. It allows the company to control the quality of the activities of state institutions and leaders and public servants need for self-control and improve the administrative process. Performance measurement problem – It is a problem, first of all, the analysis of management activities and decisions. The growing diversity of modern societies, global threats and risks, migration crisis, new geopolitical fractures - all this and much more makes higher demands to the systems of government, which not only have to respond quickly to rapidly changing reality, but also to anticipate, predict, construct this reality. What should be government controlled system in a non-linear reality to be effective? How can you determine the very effectiveness of public administration in terms valent requests and expectations of the population? Criteria and parameters of efficiency of public administration, which would have been authentic real needs of society rather than small groups of political class, is necessary both to public authorities and society itself. Her presence will allow the public to monitor the quality of the activities of state institutions, and government and public officials – to improve the quality of public services provided to the population. The authors show that in the last decade in the evaluation of the effectiveness of public sector management prevails integrated approach that includes a set of individual indicators characterizing various aspects of the effectiveness of the government. In official documents containing the relevant assessment methodology presents different approaches to the formation, the system of indicators, which are used in different countries in order to measure the quality of public services provided by the public authorities. However, this quantification of the quality of public services provided at various levels of government in the Russian Federation, still needs both theoretical reflection and building the mechanisms of its implementation in practice of public administration in view of Russian realities.
Keywords: government effectiveness, criteria and parameters of efficiency, system of government, legitimacy and legality control